2009
DOI: 10.1002/polb.21714
|View full text |Cite
|
Sign up to set email alerts
|

POSS‐nylon 6 nanocomposites: Influence of POSS structure on surface and bulk properties

Abstract: Hybrid organic/inorganic nanocomposites based on polyhedral oligomeric silsesquioxane (POSS) nanostructured chemicals and nylon 6 were prepared via melt mixing. Two structurally and chemically different POSS molecules, a closed cage, nonpolar octaisobutyl POSS (Oib-POSS) and an open cage, polar trisilanolphenyl POSS (Tsp-POSS) with differing predicted solubility parameters were evaluated in the nylon matrix. Surface analysis, including quasi-static and dynamic nanoindentation and nanotribological techniques, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 50 publications
4
48
0
2
Order By: Relevance
“…Generally overlooked in these systems is the low critical solubility of POSS in most polymers. Previous work has explored the solubility parameters of POSS-polymer combinations, in order to make predictions about dispersion and compatibility [15][16][17]; such methods produce inaccurate results. We have demonstrated that even with excellent matches in compatibility between POSS and matrix fillers, often as not the outcome is plasticization or antiplasticization of the polymer [18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally overlooked in these systems is the low critical solubility of POSS in most polymers. Previous work has explored the solubility parameters of POSS-polymer combinations, in order to make predictions about dispersion and compatibility [15][16][17]; such methods produce inaccurate results. We have demonstrated that even with excellent matches in compatibility between POSS and matrix fillers, often as not the outcome is plasticization or antiplasticization of the polymer [18].…”
Section: Introductionmentioning
confidence: 99%
“…modulus, strength, glass transition temperature, mechanical performance and thermal stability [5,6,[11][12][13][14][15]. Changes in the physical properties of the host polymer are usually attributed to the molecular aggregation of the POSS molecules themselves which then serve to reinforce the polymer network by acting as nucleating agents or plasticisers, which can influence the final crystalline morphology by either retarding or increasing the host polymer's crystallisation process.…”
Section: Introductionmentioning
confidence: 99%
“…78 They are used as a surface coating agent, but can also be added to a polymer and self-segregate to the surface, allowing hydrophilic polymers to be converted to hydrophobic polymer surfaces without extra processing steps. 85 This method also adds a roughness on a nanometer scale to the surface, due to the aggregation of the POSS molecules, which could be considered to be molecular particles.…”
Section: Ice Resistancementioning
confidence: 99%